Absolute derivative of set-valued maps - Muslikh, Mohamad; Kilicman, Adem (Universiteti i Prishtines Prishtine, Kosovë, 2022)
The aim of this article is to develop a differential calculus for setvalued functions with values in metric spaces of the family of all compact and convex subsets. Using only the metric Hausdorff on metric spaces and without using the Hukuhara difference, a concept of the derivative is introduced for set-valued functions in such metric spaces. The comparison with the other derivative definitions of the set-valued functions and the relation to the Lipschitz conditions was also investigated in this paper.